Jogos Escolares de Minas Gerais: política pública, experiências e processos de formação de professores de Educação Física - Felipe dos Santos Senra (2020)
In this work, I present results of research where the objective was to describe and analyze the experiences of Physical Education teachers with the School Games of Minas Gerais - JEMG. This research had a qualitative character, seeking to understand the meanings of school games and the sports phenomenon attributed by the teachers, subjects of the research. To this end, semi-structured interviews were conducted with eight PE teachers, from different teaching networks. As a methodology to analyze the data, content analysis was used as inspiration, through pre-analysis techniques, material exploration, and treatment of results. The JEMG is an action of the Government of Minas Gerais, carried out by two secretariats, SEDESE (Secretaria de Estado de Desenvolvimento Social) and SEE (Secretaria de Estado de Educação) whose execution of the event is done by FEEMG. We found contradictions between the stated objectives of the event and its actions and characteristics. The speech states that competition is a pedagogical tool, which helps in the construction of citizenship, in an educational and democratic way, where sociability and integration are sought. However, its actions seek to develop a sports competition with the characteristics of high-performance sport. Such an event occurs under precarious conditions for the development of this public policy: working conditions, materials and infrastructure, and didactic-pedagogical relations, consisting of a “precarious promotion” of sport as a social right. We seek an articulation between my teaching experiences and the experiences of teachers, understanding the teachers interviewed as “territorial subjects”, where things happen to them. We perceive between teachers differents and conflicting views about sport, pedagogical practices, and the JEMG. Their backgrounds and experiences, from childhood to the present day, have influenced/influence these relationships, presenting different practices, thoughts, objectives, experiences, and reasons for participating or not in this event. Such differences are present in the teachers' narratives when they see changes and dreams for school games. If, on the one hand, specific ideas regarding the organization, conditions of participation, and forms of dispute arose, on the other hand, they envisioned and dreamed of sporting festivals that would allow greater access to students. We call the provisional summaries of this work “viable unpublished”. The first viable first would be to dream about pedagogical practices and to play games under less precarious conditions. In addition, the problematization among students of issues related to competition, selectivity, meritocracy, as well as the characteristics of the modern sport was identified as possibilities. The other viable first would be to build spaces of dialogue with teachers in our field of professional activity in order to reflect and organize school sports events based on other principles, objectives, and forms. The process of building the event becomes as important as the event itself because it can allow its actors to debate, reflect and be authors of their own practices, in a perspective of democratic management of sport in schools as a social right.